Biogeochemical interactions of natural organic matter with arsenic in groundwater - Kulkarni, Harshad Vijay (Kansas State University, 2016)
Groundwater contamination with arsenic (As), a naturally occurring metalloid, is a worldwide problem. Over 100 million people are at health risk due to arsenic contaminated groundwater, especially in the Bengal Basin in south-east Asia. Dissolved organic matter (DOM), geology and geomicrobiology are important factors affecting arsenic mobility. This study focuses on interactions of different aspects of natural organic matter in arsenic-contaminated environments. A literature review specifically includes past studies done on fundamentals of arsenic geology, geomicrobiology, DOM characterization and relevant analytical methods and tools. Based on background information already collected, this research is focused on specific research questions and corresponding hypotheses. The overarching goal of this investigation is to better understand the mechanisms by which DOM influences arsenic mobilization. The specific goals of this research are: 1) to evaluate role of oxidized humic quinones in reductive dissolution of Fe-As minerals and subsequent arsenic mobilization via electron shuttling, 2) to quantify the rate of microbially mediated reductive dissolution in the presence of oxidized humic quinones, 3) to evaluate DOM-Fe-As ternary complex formation and its influence on arsenic mobility and 4) to characterize DOM in the arsenic-contaminated aquifers of West Bengal, India and evaluate its role in arsenic mobilization using groundwater flow and contaminant transport modeling approach. Results of this study revealed that oxidized quinone like moieties (such as fulvic acids) serve as an electron shuttle and enhance the reductive dissolution process under reducing conditions, hence mobilize the arsenic in groundwater. Another key result from this study suggested that arsenic binds with non-aromatic portion of the humic-like DOM under reducing conditions and increases its solution concentration. A field study conducted in West Bengal, India revealed that the mechanisms studied in the laboratory exists in reducing aquifer. A groundwater flow and reactive transport model was created to explain multiple interactions of DOM and arsenic spatial scales. Broader impacts of this study include significant addition to scientific knowledge about subsurface biogeochemistry and the role of DOM in biogeochemical reactions in the subsurface.
Keywords: Arsenic Biogeochemistry; Biogeochemical Modeling; Dissolved Organic Matter Characterization; Environmental Engineering; Fluorescence Spectroscopy and PARAFAC; Groundwater Flow and Reactive Transport Modeling